A SEM ANALYSIS OF THE IMPACT OF UNETHICAL STAKEHOLDER BEHAVIORS ON CONSTRUCTION PROJECT FAILURES: AN OIL AND GAS INDUSTRY STUDY - Pittayaporn Gomarn; Jakrapong Pongpeng (My University, 2022)
Continued unethical behavior by stakeholders within the oil and gas construction industry has a possible impact on the failure of many projects. This study therefore aims to investigate the impact of this type of behavior on the oil and gas construction industry. A conceptual framework was developed from both a literature review and interviews with 8 experts working on oil and gas construction projects in Myanmar, Malaysia and Thailand. A 31-item questionnaire was used to measure the 304 responses, from which a confirmatory factor analysis and structural equation model (SEM) were developed to investigate this impact. The results revealed that the most significant direct impact on a project’s failure was a main contractor’s unethical behavior. Furthermore, the study determined that the unethical behaviors of the consultant and designer had no direct impact on a project’s failure but that there was an impact of the owner’s unethical behavior. Ranked in order of importance, the indicators of a project failure are as follows: stakeholders' dissatisfaction; cost overrun; time overrun; negative effects on health, safety and environment; quality defects; and dispute and litigation. The results provide a guideline for developing a code of ethics to conduct unethical behavior investigations, which will help decrease future project failures
Keywords: Cost overrun; Construction Project Management and Performance